Pengaruh Motivasi, Kepuasan Kerja dan Disiplin Kerja terhadap Kinerja Karywan pada PT. Bahtera Bahari Shipyard di Kota Batam - Dhiya Ulha Qiyah; Mauli Siagian (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2021)
This study aims to determine empirically about the influence of motivation, job satisfaction and work discipline on the performance of the employees of PT Bahtera Bahari Shipyard. A sample of 155 respondents. The instrument used to collect data was a questionnaire. The sampling technique used is Random Sampling where sampling provides equal opportunities for each element or member of the population to be selected as a sample. Test data in this study are validity, reliability, classic assumptions, multiple linear analysis of the coefficient of determination (R2), t-test and f test. The data were processed using SPSS version 25. The results of the study found t count> t table is 4.807> 1.976 and significant value of 0.000 <0.05. This means that motivation has a positive and significant effect on the performance of employees of PT Bahtera Bahari Shipyard. t calculate the known job satisfaction> t table is 2.290> 1.976 and a significant value of 0.000 <0.05. This means that job satisfaction has a positive and significant effect on the performance of the employees of PT Bahtera Bahari Shipyard. t calculate known work discipline> t table is 4.174> 1.976 and a significant value of 0.000 <0.05. This means that the work discipline has a positive and significant effect on the performance of the employees of PT Bahtera Bahari Shipyard. And there is motivation, job satisfaction, and employee discipline together have a positive and significant effect on employee performance. Evidenced by the results of the F test (simultaneous) F value of 27,197 (Fcount)> 3.05 (Ftable). And the value is significant at 0,000 <0.05.